The Permanence and Indissolubility of Marriage Against the Background of Deuteronomy 24:1 - Grzegorz Bzdyrak; Przemysław Kubisiak (Religions)
This article is an interdisciplinary study. The authors (a canon lawyer and a biblical theologian) endeavour to examine the text of the Book of Deuteronomy 24:1 through both canonical and exegetical lenses. They look at whether and to what extent it is aligned with the contemporary Catholic teaching on the permanence and indissolubility of marriage. They frame the research problem through a series of questions: Is the analysed text contrary to the Catholic Church’s position on the inadmissibility of divorce? Does it imply consent to divorce? Or does it permit marital separation but solely under specific conditions? First, the authors discuss the Catholic teaching on the permanence and indissolubility of marriage. They highlight a distinction between the two terms. They seek to expose the process of evolution of the institution of marriage from the Creation, i.e., God’s original intention in relation to marriage, through the Old Testament period of “hardness of heart”, i.e., from the original sin to the time of Jesus, to the third stage since Jesus, who restored the original order destroyed by sin and elevated the conjugal bond of two baptized people to the dignity of a sacrament. The authors then examine the concept of marital separation. By its very nature, it does not sever the marital bond. The authors explain the legal grounds for separation, among them adultery and failure to maintain marital fidelity. Next, they conduct an in-depth semantic analysis of the studied text and discuss divorce proceedings in the light of Deuteronomy 24:1. They close the discussion with conclusions. Due to the interdisciplinary nature of the work, the authors relied on the literature from the domains of biblical studies and canon law.